Brain drain, exodus and chicken run : media discourses on emigration - Bright, Sue-Ann (Rhodes University, Faculty of Humanities, Department of Psychology, 2005)
This paper explores the discourses of emigration in a South African daily newspaper from 1988 to 2001, and discusses the implications of these discourses on the way in which emigration is constructed within South African society In this paper, Potter and Wetherell 's (1987) approach to discourse analysis is utilized. It makes use of interpretative repertoires, to explore the functions and consequences of the discourses. The discursive framework thereby reveals the different subject positions related to nationalism, race and class. It is argued that economics and notions of culture and social class, do more than provide a useful medium through which the phenomenon of emigration can be understood. They also support the affirmations of certain groups of people above others, by claiming that emigration is unpatriotic and disloyal. This paper concludes by identifying the negative connotations of media discourses in the construction of emigration and acknowledges that many alternate constructions are silenced in this matter.
Keywords: Mass media and language -- South Africa; Mass media criticism -- South Africa; Discourse analysis -- Social aspects